Answer:
x⁴ + x³ + 4x² - 5x
Step-by-step explanation:
The polynomials given in the question are:
x⁴ - 3x + 1
4x² - 2x + 8
x³ - 9
We have to add all them
First write all the polynomial in the summation form:
(x⁴ - 3x + 1) + (4x² - 2x + 8) + (x³ - 9)
Open the brackets:
x⁴ - 3x + 1 + 4x² - 2x + 8 + x³ - 9
Group together the similar terms
(x⁴) + (x³) + (4x²) + (-3x -2x) + (1 + 8 - 9)
Finding the sum in brackets:
x⁴ + x³ + 4x² + (-5x) + (0)
x⁴ + x³ + 4x² - 5x
Note that the sum is in descending powers of x
The question mark is equal to -5 and if you need f than f is equal to -15
Answer:
v = sqrt(473)
Step-by-step explanation:
v^2 = u^2 +2as
Let u = 9 a = 7 and s = 28
v^2 = 9^2 +2(7)(28)
v^2 = 81 + 392
v^2 = 473
Take the square root of each side
sqrt(v^2) = sqrt(473)
v = sqrt(473)
Distribute 7 to n-3.4 which is 22.5 + 7n - 23.8